2020
DOI: 10.2147/cmar.s264582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perineural Invasion and Postoperative Complications are Independent Predictors of Early Recurrence and Survival Following Curative Resection of Gastric Cancer</p>

Abstract: Purpose: To investigate the clinicopathological and prognostic factors related to early gastric cancer recurrence after curative resection. Patients and Methods: Between October 2006 and August 2018, a total of 149 patients with recurrence of gastric cancer/adenocarcinoma of the esophagogastric junction after curative resection were enrolled from our treatment group. A retrospective clinical analysis was performed on these patients with gastric cancer recurrence after curative resection. Results: Among the 149… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Consistent with our study, previous studies have also revealed that larger tumor size, advanced AJCC stage, undifferentiated type, and presence of lymphatic or vascular invasion are associated with PNI positivity [ 14 , 16 , 17 , 18 , 19 ]. PNI is not only a signature feature of advanced GC but may also contribute to poor outcomes in the setting of relatively early disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our study, previous studies have also revealed that larger tumor size, advanced AJCC stage, undifferentiated type, and presence of lymphatic or vascular invasion are associated with PNI positivity [ 14 , 16 , 17 , 18 , 19 ]. PNI is not only a signature feature of advanced GC but may also contribute to poor outcomes in the setting of relatively early disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study found that PNI was an independent predictor of hematogenous metastasis in node-negative advanced GC [ 20 ]. Chen et al also observed that PNI was an independent factor associated with early recurrence and poorer survival in patients with stage I–III GC after curative surgery [ 17 ]. Furthermore, two meta-analyses revealed that PNI independently affects DFS and overall survival in patients with resectable GC [ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survival analysis showed that perineural invasion (P = .011) and postoperative complications (P = .007) were independent prognostic factors. [15] Another study in China by 417 gastric cancer patients exhibited that there was no significant difference in recurrence patterns between early and late recurrence (P < .05 each). For pT1 stage gastric cancer, tumor size (P = .011) and pN stage (P = .048) were associated with early recurrence of gastric tumors.…”
Section: Discussionmentioning
confidence: 96%
“…For a further validation of the significant association observed between risk factors and 10-year survival after breast cancer surgery, Table 6 lists selected studies that have identified risk factors for poor survival after breast cancer surgery [ 24 , 30 , 32 , 33 , 34 , 35 , 36 ]. As in these previous works, our study demonstrated that the preoperative SF-36 PCS score, preoperative SF-36 MCS score, postoperative recurrence, and tumor stage are significantly associated with 10-year survival after breast cancer surgery ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%